An environmentally friendly and low-cost catalyst for Li–CO2 batteries based on Co recovered from waste lithium-ion batteries. Issue 3 (1st February 2023) - Wu, Hongkun; Wang, Zhen; Zeng, Xiaoyuan; Fei, Zitong; Gu, Yang; Ding, Kai; Dong, Peng; Zhang, Yingjie; Meng, Qi
Abstract: With the use of lithium batteries increasing year by year, resulting in a large number of waste lithium-ion batteries generated, bringing pressure to the ecological system while also causing a waste of Co resources. Although Co-based catalysts are also of interest in the Li–CO2 system, no research has been reported on the preparation of catalysts for value-added utilization of recovered Co. In this paper, Li–CO2 batteries with Co3 O4 /CNT cathodes were prepared by environmentally friendly hydrothermal method employing cobalt oxalate recycled from waste lithium-ion batteries as a Co source in combination with commercial CNT. Unlike traditional noble metal and transition metal-based catalysts, which are expensive and complicated, this work can further reduce the cost of batteries by recycling valuable Co sources from waste lithium-ion batteries. As a result, the battery has the discharge capacity of 2728 mAh g −1 at a current density of 100 mA g −1 . Not only that, but it can reach more than 85 cycles at a limited capacity of 400 mAh g −1 .